Crítica rousseauniana da imitação teatral: da recusa do teatro de classe francês ao consentimento da festa - TAVARES, Márcio Júnior Montelo (2017)
In the present bibliographical research, the theater is analyzed, under a critical perspective, as an imitation of the social representation in the writings of JeanJacques Rousseau, taking as a parameter the criticism elaborated by the philosopher genebrino on the French theater, especially in what concerns The comedy of customs advocated by thinkers such as Voltaire and D'Alembert, as well as his negative response to the question about the contribution of the sciences and the arts to the moral improvement of man, presented in his First Discourse. In this panorama, Rousseau disproves most of the philosophers of his time, showing that art, instead of elevating man to a higher moral level, corrupts it by making it vile and attached to frivolities and luxuries unnecessary to a society Virtuous Indeed, unlike ordinary Enlightenment thought, the Geneva philosopher did not assert that this society and that historical moment in which he was inserted represented the pinnacle of moral progress in the history of human civilization, but rather preached that the man had entered a dangerous Process of moral degeneration, of narcissism, from which the other is taken as a mere projection of itself. In this way, we are dealing with the French theater considerations of some Enlightenment philosophers, as well as the answer given by Rousseau to D'Alembert in the famous missive on the Geneva entry in Diderot's Encyclopaedia. It is concluded that, while recognizing the importance of the sciences and the arts for humanity, Rousseau viewed such dimensions of knowledge as harmful insofar as they served distorted purposes, especially when used as a form of distinction between men. The theater, conceived in this perspective, had the function of being simple distraction for the masses, being mere caricature of the daily life.